Caputo Type Fractional Differentiation for the Extended Generalized Mittag-Leffler Function - UÇAR, FARUK (My University, 2023)
The goal of this paper is to develop some differential equation formulas for the extended generalized Mittag-Leffler function (EGMLF) using Caputo type Marichev-Saigo-Maeda (MSM) fractional derivative operators involving the third Appell function as kernel, with the results viewed in the context of extended Wright hypergeometric type function. Furthermore, we highlight their relation to previously known results.
Keywords: Matematik; Bilgisayar Bilimleri; Temel Bilimler; Mathematics; Computer Science; Natural Sciences; Temel Bilimler (SCI); MATEMATİK, UYGULAMALI; Natural Sciences (SCI); MATHEMATICS; MATHEMATICS, APPLIED; Analiz; Fizik Bilimleri; Uygulamalı matematik; Analysis; Physical Sciences; Applied Mathematics; Extended Mittag-Leffler function; extended Wright-type hypergeometric functions; fractional integral and derivative operators; Extended Mittag-Leffler function; fractional integral and derivative operators; extended Wright-type hypergeometric functions